Physicians’ Knowledge, Perceptions, and Attitudes Related to Patient Confidentiality and Data Sharing - Karasneh, Reema (Int J Gen Med, 2021)
BACKGROUND: The protection of patient confidentiality is an essential practice for the successful provision of healthcare. This study examines physicians’ knowledge and attitudes related to data sharing and patient confidentiality. METHODS: This is a descriptive, questionnaire-based study. Physicians were invited via e-mail to complete the study survey. The survey comprised three sections related to knowledge, attitudes, and demographic characteristics. RESULTS: A total of 221 physicians, with varying levels of experience and from a range of specialty areas, completed the study survey. Ethical dilemmas were encountered annually by physicians specialized in family medicine and daily by physicians in internal medicine wards more often than those in other departments. The mean score for knowledge was 7.34 (out of 14; SD=2.92) and had a positive correlation with attitudes towards the protection of data confidentiality (r(2)=0.282, p<0.001). Undergraduate courses were the main source of knowledge related to ethical issues (167; 74.9%). Sex (B=-1.47, p=0.001), marriage (B=-1.198, p=0.021), and source of consultation (B=-.248, p=0.02) were all found to predict knowledge scores. Likewise, attitudes were predicted by experience (B= 0.279, p<0.001), sex (B= -2.797, p=0.002), marriage (B=1.91, p=0.02), and number of ethical dilemmas faced (B=1.695, p <0.001). CONCLUSION: Physicians from different departments were found to lack sufficient knowledge about many aspects of patient confidentiality. While some of the physicians’ practices complied with the law, other practices were identified as patient confidentiality breaches.